Analyzing patient‐reported outcome data when completion differs between arms in open‐label trials: an application of principal stratification. Issue 10 (13th August 2019) - Roydhouse, Jessica K.; Gutman, Roee; Bhatnagar, Vishal; Kluetz, Paul G.; Sridhara, Rajeshwari; Mishra‐Kalyani, Pallavi S.
Abstract: Purpose: Cancer trials are often open‐label and include patient‐reported outcomes (PROs). Previous work has demonstrated that patients may complete PRO assessments less frequently in the control arm compared with the experimental arm in open‐label trials. Such differential completion may affect PRO results. This paper sought to explore principal stratification methodology to address potential bias caused by the posttreatment intermediate variable of questionnaire completion. Methods: We evaluated six randomized trials (five open‐label and one double‐blind) of anticancer therapies with varying levels of PRO completion submitted to the Food and Drug Administration (FDA). We applied complete case analysis (CCA), multiple imputation (MI), and principal stratification to evaluate PRO results for quality of life (QOL) and the domains of physical, role, and emotional function (PF, RF, and EF). Assignment to potential principal strata was by the expectation maximization algorithm using patient baseline characteristics. Results: Completion rates in the experimental arm ranged from 66% to 94% and 51% to 95% in the control arm. Four trials had negligible completion differences between arms (1%‐2%), and two had large differences favoring the experimental arm (15%‐17%). For trials with negligible completion differences, principal stratification results were similar to CCA and MI results for all domains. Notable differences in point estimates may be observed in trials with large differences in completion rates. However, in the examined trials, the confidence intervals for the principal stratification estimates overlapped with the ones obtained using CCA. Conclusions: The principal stratification estimand may be a useful additional analysis, especially if PRO completion differs between arms.